Simulation of the Behavior of Non-Newtonian Fluids Dissolved in Water Inside Non-Concentric Rotating Cylinders - Abolfazl Hajizadeh Aghdam; Mohamadjavad Ebrahimi; Ahmad Beytolahi Tavakoli; AmirHossein Refahi (مجله مدل سازی در مهندسی)
The study and investigation of the currents passing through non-concentric annular cylinders is of great importance due to its application in many fields such as oil and petrochemical industries. Oil well drilling is an example of this application. In the current research, non-Newtonian fluid is considered between two non-concentric cylinders rotating. The changes in the speed of the rotating cylinder and as a result the changes in the radial speed, axial speed, and tangential speed of the fluids were investigated along the selected planes. Turbulence kinetic energy and shear stress on the cylinder walls, which are effective factors in fluid flow, were also analyzed and investigated. Also, in this research, a study was conducted on several non-Newtonian fluids, such as bentonite, carboxyl methyl cellulose, and xanthan gum dissolved in water, in comparison with water. Two fluids, XG and CMC, had the most similarities with the rheological properties of water, while the XG fluid kept its rheological properties at high speeds. The simulations were compared with the experimental results available in the literature, and a good agreement was observed between the results..